The Effect Playing Online GamesOn The Players - Christopher Akami J.S (SISFORMA, 2014)
Online game is a game that requires internet connection to play and while playing a lot of individuals do not care about a lot of things. Games can also influence the gamers to have bad behavior. However, playing online games can be exciting although only playing for a moment.